The contribution of the political, educational and economic factors of the citizen security in Lima - Espinoza Altamirano, Manuel Jorge (2017)
The present research is aimed to establish the contribution of the political, educational and economic factors in the Citizen security in Lima as the main existing problem the insecurity at the district and national level. For the development of this research the qualitative, quantitative, correlational and transversal method was used. The type of study is analytical, descriptive and application. For the development of this research used statistical tools and data collection from primary sources such as questionnaires and interviews and data collection through secondary sources. As primary sources of data were the 43 districts of Lima and whose total sample is 384 respondents regarding factors of political, educational and economic order and its impact in the security citizen in every district town. The results show that education and economic and political factors are important variables that determine the level of Citizen Security.Conclusions and proposals of the research is important to consider that public safety is a state policy that is the responsibility and commitment of the government, which should outline policies and strategies to deal effectively with the major problems of crime, violence , perception of insecurity and corruption. The latter existing at different levels of internal order and administration of justice such as the National Police, the Judiciary and the Public Ministry in Lima and in the country. Also it should take into account the recommendations made in more detail at the level of political, educational and economic order proposed in this research.